AI and mission: Answers to questions on mission to AI and evaluation of the replies - Pieter Verster (Pharos Journal of Theology)
Artificial intelligence (AI) has implications for all aspects of science, including the science of mission. However, the dangers of AI are also obvious, namely lack of logical explanation and human involvement, leading to plagiarism. It is interesting to ask AI questions regarding mission. What will the answers be to questions such as What is mission? What is Christian mission? What is evangelism? One must understand the limited number of answers put forward by AI regarding these different views. This article addresses the answers provided by ChatGPT regarding mission, Christian mission, and evangelism. It discusses these issues and their implications. It is important to note that AI does not have an understanding of mission, Christian mission, and evangelism. AI is a rather limited application. This article establishes that, from the perspective of mission theology, it is important to conclude that a broader and much more influential aspect of mission should be addressed. Mission has many implications that were not included in the previous understanding of mission. It seems that AI is still connected to earlier understandings of mission and does not consider new developments that are very important for understanding mission. Therefore, a full understanding of mission should be viewed from theologians and from Scripture that have implications for understanding what it entails .